Leaving Money on the Table - Mackenzie Alston; Tatyana Deryugina; Olga Shurchkov (Institute of Labor Economics (IZA), 2025)
There is much disagreement about the extent to which financial incentives motivate study participants. We elicit preferences for being paid for completing a survey, including a one-in-twenty chance of winning a 100 electronic gift card, a guaranteed electronic gift card with the same expected value, and an option to refuse payment. More than twice as many participants chose the lottery as chose the guaranteed payment. Given that most people are risk averse, this pattern suggests that factors beyond risk preferences—such as hassle costs—influenced their decision-making. Almost 20 percent of participants actively refused payment, demonstrating low monetary motivation. We find both systematic and unobserved heterogeneity in the characteristics of who turned down payment. The propensity to refuse payment is more than four times as large among individuals 50 and older compared to younger individuals, suggesting a tradeoff between financially motivating participants and obtaining a representative sample. Overall, our results suggest that modest electronic gift card payments violate key requirements of Vernon Smith's induced value theory.
Keywords: C83; C90; 330; induced value theory; motivation; incentives